Penguatan Kader Dan Guru Paud Dalam Edukasi Gizi Cegah Stunting di Wilayah Puskesmas Prambon - Aulia, Salma Shafrina; Nurjanah, Hanna; Utami, Fista; Dewi, Novianti Tysmala; Sholakhuddin, Ahmad; Andini, Novias Kemala (STMIK Royal, 2025)
Child stunting remains a significant public health concern, partly attributed to the suboptimal role of community health cadres and early childhood education teachers in delivering nutrition education. Inadequate training and various challenges in community engagement have limited the effectiveness of stunting prevention efforts. This outreach program aimed to improve the knowledge of posyandu (community health post) cadres and early childhood education (PAUD) teachers on stunting prevention and the importance of balanced nutrition to support child development. A total of 63 participants, including 50 posyandu cadres and 13 PAUD teachers, attended the activity, which included interactive lectures, discussions, and pre- and post-tests. The materials covered exclusive breastfeeding, balanced complementary feeding (MPASI), and regular monitoring of child growth and development. The results showed a significant increase in participants’ understanding, particularly regarding the impact of stunting and monitoring of child growth and development. Nutrition education proved effective in enhancing the capacity of cadres and teachers as strategic partners at the community level. It is recommended that regular follow-up training with practical approaches, such as menu planning and supplementary feeding management, be conducted to ensure program sustainability.Keywords: child development; community health post cadres ; early childhood teachers; nutrition education; stunting prevention Abstrak: Stunting pada anak masih menjadi masalah kesehatan masyarakat, salah satunya disebabkan oleh kurang optimalnya peran kader dan guru PAUD dalam edukasi gizi. Minimnya pelatihan serta kendala saat mendampingi masyarakat membuat upaya pencegahan stunting belum maksimal. Kegiatan penyuluhan ini bertujuan untuk meningkatkan pengetahuan kader posyandu dan guru PAUD mengenai pencegahan stunting dan pentingnya gizi seimbang untuk mendukung tumbuh kembang anak. Sebanyak 63 peserta terdiri atas 50 kader posyandu dan 13 guru PAUD mengikuti kegiatan yang dilaksanakan melalui ceramah interaktif, diskusi, serta evaluasi pre-test dan post-test. Materi meliputi ASI eksklusif, pemberian MPASI bergizi seimbang, serta pemantauan tumbuh kembang anak secara berkala. Hasil evaluasi menunjukkan peningkatan signifikan dalam pemahaman peserta, terutama terkait dampak stunting dan pemantauan tumbuh kembang anak. Edukasi gizi terbukti efektif dalam memperkuat kapasitas kader dan guru sebagai mitra strategis di tingkat komunitas. Disarankan agar pelatihan lanjutan dengan pendekatan aplikatif seperti penyusunan menu dan pengelolaan PMT dilakukan secara berkala untuk mendukung keberlanjutan program.Kata kunci: tumbuh kembang anak; posyandu; guru PAUD; edukasi gizi; kader posyandu; pencegahan stunting